DISCIPLINE-BASED VS. SPIRAL LEARNING APPROACH TO SCIENCE EDUCATION: A CRITICAL ANALYSIS IN THE PHILIPPINE SETTING - Pacala, Frank Angelo Abayog (Sanata Dharma University Yogyakarta, 2023)
The Philippines started the K to 12 curricula and spiral progression approach in 2012 turning back from the discipline-based curriculum. Many educators and researchers that it is a must to transfer to the spiral progression approach. This paper examined and evaluated both approaches based on various literature in the context of the Philippines since many people have appealed to go back to the old system. There is overwhelming literature that suggests the benefits of the spiral progression approach in terms of the academic achievement of students and mastery of learning. There was much literature also saying that there is a wide-ranging need for improvement in this spiral progression and K to 12 curricula as a whole. Being said, the country should overhaul the system but not abolish it. There are more benefits than harm in the spiral progression and K to 12 systems.